Drivers and barriers to successful solid waste management: assessing through an aggregated indicator - Deus, Rafael Mattos [UNESP]; Esguícero, Fábio José [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP]; Jugend, Daniel [UNESP] (Springer Nature, 2022)
Solid waste management is the main topic of the circular economy and remains a challenge for public management, because despite the recent economic downturn in Brazil, some indicators still need to be improved. This study aimed to evaluate the environmental efficiency (eco-efficiency) of municipal solid waste (MSW) management in small municipalities in the State of São Paulo (Brazil) using an aggregated indicator with data envelopment analysis. In addition, the study also aimed to rank the municipalities according to an eco-efficiency index. After the ranking, the study identified the critical factors for the success of municipalities with greater eco-efficiency index and identified the barriers to the implementation of a successful management process involving MSW management. For the most eco-efficient municipalities, the degree of waste separation at the household level stood out. The results also highlighted the importance of recyclable waste pickers in addition to recycling awareness campaigns supported by the municipalities. Education is a key aspect of improving indicators. In general, the indicator is important to assist and guide in improving the performance of municipalities.
Keywords: Eco-efficiency; Indicator; Management practices; Solid waste; Sustainability